1985
DOI: 10.1159/000153505
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty in Identification of Blood Group A Subtypes by Agglutination Test

Abstract: Identification of the blood group A subtypes, i.e. A1, A2, and A1-A2 intermediate (Aint), by agglutination test, particularly in AB red cells, is ambiguous. The expressions of A subtypes in red blood cells are the consequences of diverse formations of the A substances by the action of three types of blood group N-acetyl-galactosaminyl-transferases controlled by A1, A2, and Aint genes. Therefore, the A subtypes are more directly identified by exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1987
1987
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…However, although present, it was not al ways possible to decide whether a sample belonged to Ain, subgroup [see also Yoshida et al, 1985], Suspected Ajnt were in cluded with Ai in the frequency calcula tions.…”
Section: Abo Blood Groupsmentioning
confidence: 99%
“…However, although present, it was not al ways possible to decide whether a sample belonged to Ain, subgroup [see also Yoshida et al, 1985], Suspected Ajnt were in cluded with Ai in the frequency calcula tions.…”
Section: Abo Blood Groupsmentioning
confidence: 99%
“…A subgroups like A 2 or others may have anti-A 1 antibody reactive at 37°C and should receive either O group or same group packed red cells but not A 1 red cells [1]. Yoshida et al showed in a study that an individual can be even A int B group and plasma enzyme determination is better than routine serological methods in determination of A 1 , A 2 , or A int subtypes [9,10].…”
Section: Discussionmentioning
confidence: 99%